On The Theme Of Marketing Communication Side Effects - Zich, František (Communication Today, 2025)
This article covers the issues of complex impacts of marketing communication on society. It focuses in particular on side effects, unwanted consequences of advertising. Based on data from an empiric survey which was focused on the target group of younger respondents with completed secondary and university education, it presents its fi ndings about traceability of advertising and perception of side effects of advertising messages. It has been confi rmed that a larger part of respondents does not deal with side effects of advertising; they do not know or cannot assess what are overall side effects of advertising on society. In assessment of ads promoting individual types of products, however, the side, unwanted effects are reported. However, rather negative social effects of advertising of the promoted product prevail. The achieved fi ndings contribute to the methodology of recognition of the complex impact of marketing communication, especially of advertising, on society.